The American pipe dream : performance of drug addiction, 1890-1940 - Shulman, Max, 1980- (Studies in theatre history and culture., 2022)
"The American Pipe Dream examines the representational history of addiction on the U.S. stage from 1890 to the start of the nation's involvement in the second World War in 1941. Through intensive archival work, textual and performance analysis, and by considering related literary, legislative, and medical histories, this work argues that performance was essential in the creation of the drug addict in the U.S. cultural imagination. Though little attention has been paid to the figure of the stage-addict, this conventionalized figure was a major presence in U.S. popular entertainment through the Progressive Era into the Roaring Twenties, and through the Great Depression. The aim of this study is to trace this complex history, establish the stage-addict's place in U.S. theatre studies, and, by doing so, provide a new lens for examining the history of drug addiction and drug use in the U.S"--